Pola Konsumsi Produk Skincare Bedasarkan Sosial & Budaya Remaja Putri : Studi Deskriptif Di SMK Negeri 15 Jakarta - Dian Alfia Purwandari; Achmad Nur Hidayaht (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Skincare is a series of activities aimed at maintaining healthy skin, improving appearance and reducing facial skin problems. The skin care process can also provide the nutrients needed to protect the skin from the negative effects of excessive sunlight. Skincare itself has many benefits for its users which are differentiated by each skincare product consumed. One of the efforts made by companies to increase sales value and meet consumer demand for consuming skincare is to provide detailed and clear information (Teng & Jusoh, 2013). This information is provided in the form of listing the raw materials used, production date, method of use and distribution permit issued by BPOM, as well as halal certification obtained from LPPOM MUI.